When is it safe to eat different broiler chicken tissues after administration of doxycycline and tylosin mixture?. Issue 3 (18th February 2021) - Monir, Hany H.; Fayez, Yasmin M.; Nessim, Christine K.; Michael, Adel M.
Abstract : Abstract: Residues of veterinary drugs in poultry meat have serious health effects on humans (e.g., antimicrobial resistance, carcinogenicity, and hypersensitivity), which make the control of veterinary drug residues an important parameter in ensuring consumer protection.  This work was performed to quantitatively determine two co‐formulated anti‐infective veterinary agents, tylosin tartrate (TYT) and doxycycline hydrochloride (DOX) in different tissues of broiler chickens (liver, muscles, and fat) using high performance liquid chromatography. The chicken was treated with the recommended dose of a binary mixture of the drugs (Tydovet). Moreover, the study aimed to estimate the withdrawal time of both drugs in chicken tissues. The analysis was done by solvent extraction and solid‐phase extraction for clean‐up of samples from the tissue matrix, followed by liquid chromatographic determination of the cited drugs with UV‐detection. Residue decline with time was tracked, and both antibiotics were found to be more persistent in liver tissues than other tissues (muscle and fat). The effect of freezing and cooking was investigated on tissue residue levels. While freezing had little effect on the concentration of both antibiotics; cooking, as anticipated, led to a marked decline. Therefore, it is recommended to pay attention to the proper withdrawal periods before marketing to ensure the hygienic suitability of broilers edibles for safe human consumption. Practical Application: This novel study measures tylosin and doxycycline residues simultaneously in different tissues (muscle, fat, and liver) after administration of Tydovet powder to the broiler chicken. Residues in fat persisted for a longer time than in muscle in case of TYT, whereas the reverse was noticed in DOX.